2015
DOI: 10.1167/iovs.15-18087
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Ability of Retinal Vessel Diameter Measurements in Open-Angle Glaucoma

Abstract: The diagnostic ability of CRAE for detecting OAG was good, which was not much worse than that of average RNFL thickness. This finding suggests the potential usefulness of RVD for glaucoma detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…More recently, Yoo et al reported similar findings of retinal arteriolar narrowing in glaucoma, and further found that the diagnostic ability of retinal arteriolar calibre was comparable to retinal nerve fibre layer (RNFL) thickness in detecting OAG, which is an optimistic introduction to its potential use in clinical settings. 79 …”
Section: Retinal Vascular Changes Associated With Glaucomamentioning
confidence: 99%
“…More recently, Yoo et al reported similar findings of retinal arteriolar narrowing in glaucoma, and further found that the diagnostic ability of retinal arteriolar calibre was comparable to retinal nerve fibre layer (RNFL) thickness in detecting OAG, which is an optimistic introduction to its potential use in clinical settings. 79 …”
Section: Retinal Vascular Changes Associated With Glaucomamentioning
confidence: 99%
“…Clinical studies of ocular vascular changes associated with glaucoma have mainly focused on retinal vessel diameter (Jonas et al 1989;Ikram et al 2005;Mitchell et al 2005;Amerasinghe et al 2008;Kawasaki et al 2013;Yoo et al 2015), and the relationship with retinal nerve fibre layer (RNFL) thickness or visual field defects (Hall et al 2001;Zheng et al 2009;Tham et al 2013). For instance, a positive association was reported between decreased peripapillary arteriole diameter and visual field defects in the corresponding hemifield (Hall et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…We thank Pekel et al 1 for their interest in our work 2 and for the opportunity to discuss the findings of our study. They mentioned in their study that the mean retinal arteriolar caliber did not statistically differ between young relatives of patients with open-angle glaucoma (OAG) and age-matched healthy controls; however, we would like to point out that not all relatives of patients with OAG progress to glaucoma.…”
mentioning
confidence: 84%